Mechanism of Immunopotentiation and Safety of Aluminum Adjuvants - HogenEsch, Harm (Frontiers in Immunology, 2013)
Aluminum-containing adjuvants are widely used in preventive vaccines against infectious diseases and in preparations for allergy immunotherapy. The mechanism by which they enhance the immune response remains poorly understood. Aluminum adjuvants selectively stimulate a Th2 immune response upon injection of mice and a mixed response in human beings. They support activation of CD8 T cells, but these cells do not undergo terminal differentiation to cytotoxic T cells. Adsorption of antigens to aluminum adjuvants enhances the immune response by facilitating phagocytosis and slowing the diffusion of antigens from the injection site which allows time for inflammatory cells to accumulate. The adsorptive strength is important as high affinity interactions interfere with the immune response. Adsorption can also affect the physical and chemical stability of antigens. Aluminum adjuvants activate dendritic cells via direct and indirect mechanisms. Phagocytosis of aluminum adjuvants followed by disruption of the phagolysosome activates NLRP3-inflammasomes resulting in the release of active IL-1β and IL-18. Aluminum adjuvants also activate dendritic cells by binding to membrane lipid rafts. Injection of aluminum-adjuvanted vaccines causes the release of uric acid, DNA and ATP from damaged cells which in turn activate dendritic cells. The use of aluminum adjuvant is limited by weak stimulation of cell-mediated immunity. This can be enhanced by addition of other immunomodulatory molecules. Adsorption of these molecules is determined by the same mechanisms that control adsorption of antigens and can affect the efficacy of such combination adjuvants. The widespread use of aluminum adjuvants can be attributed in part to the excellent safety record based on a 70-year history of use. They cause local inflammation at the injection site, but also reduce the severity of systemic and local reactions by binding biologically active molecules in vaccines.